Gender, sexuality and colonial modernities - Burton, Antoinette M. (Routledge research in gender and history, 1999)
Gender, Sexuality and Colonial Modernities considers the ways in which modernity was constructed, in all its incompleteness, through colonialism. Using a variety of archival resources and equally diverse methodologies, the authors trace modernity's unstable foundations in the slippages and ruptures of colonial gender and sexual politics. As a whole, the essays illustrate that modern colonial regimes are never self-evidently hegemonic, but are always in process - subject to disruption and contest - and never finally accomplished; and are therefore unfinished business.
Keywords: 1800-1899; approches et analyses; colonialisme; discipline; europe; fem1000; féminisme décolonial; histoire; occident; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; époque moderne; études postcoloniales

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montreal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; discipline; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppression; thématiques; théologie; voiles islamiques

"Chapitre I".De l'assujettissement des femmes. - Mill, John Stuart (De l'assujettissement des femmes, 1992)
Keywords: 1800-1899; approches et analyses; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppression; thématiques

De l'assujettissement des femmes. - Mill, John Stuart (Arenes, 1992)
L´écrivain britannique John Stuart Mill était l´un des premiers écrivains masculins à se positionner pour l´égalité des sexes et à défendre la libération des femmes. Il se pencha sur la liberté économique des femmes et était de l´avis que le rôle d´une femme dans le mariage devait évoluer. Le livre « De l’assujettissement des femmes » est un classique de la littérature féministe. Le philosophe et politicien britannique John Stuart Mill (1806+1873) est un des penseurs libéraux les plus importants du 19e siècle. Il est particulièrement connu pour ses théories d´utilitarisme. Il s´est occupé de divers sujets politiques et philosophiques, dont les concepts de liberté et d´égalité des sexes.
Keywords: 1800-1899; approches et analyses; discipline; discours dominant; droits des femmes*; europe; fem1000; philosophie; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppression; thématiques